2020
DOI: 10.1155/2020/8876131
|View full text |Cite
|
Sign up to set email alerts
|

Altered Coactive Micropattern Connectivity in the Default-Mode Network during the Sleep-Wake Cycle

Abstract: The default-mode network (DMN) is believed to be associated with levels of consciousness, but how the functional connectivity (FC) of the DMN changes across different states of consciousness is still unclear. In the current work, we addressed this issue by exploring the coactive micropattern (CAMP) networks of the DMN according to the CAMPs of rat DMN activity during the sleep-wake cycle and tracking their topological alterations among different states of consciousness. Three CAMP networks were observed in DMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…In the pDMN, the posterior DMN structures displayed higher levels of activity (mean normalized activity: 0.3382 ± 0.0094), whereas the anterior DMN regions exhibited relatively lower levels of activity (mean normalized activity: 0.2708 ± 0.0021). The structures of all CAMPs were similar to those in our previous work [35]. It could be observed that the cDMN was the primary activity pattern of the DMN in the SWS state (Figure 4(a)), and the aDMN and pDMN were the major activity patterns in the REM sleep state in all three sleep periods (Figure 4(b)).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…In the pDMN, the posterior DMN structures displayed higher levels of activity (mean normalized activity: 0.3382 ± 0.0094), whereas the anterior DMN regions exhibited relatively lower levels of activity (mean normalized activity: 0.2708 ± 0.0021). The structures of all CAMPs were similar to those in our previous work [35]. It could be observed that the cDMN was the primary activity pattern of the DMN in the SWS state (Figure 4(a)), and the aDMN and pDMN were the major activity patterns in the REM sleep state in all three sleep periods (Figure 4(b)).…”
Section: Resultssupporting
confidence: 77%
“…The other one is the construction of CAMP networks that correspond to the FC structures across brain regions for these CAMPs. Systematic descriptions of the CAMP algorithm and the CAMP network method have been presented in our prior publications, which were capable of revealing the dynamic configurations of DMN activity during the sleepwake cycle [35,36].…”
Section: Camp Algorithm and Camp Network Methodsmentioning
confidence: 99%
See 1 more Smart Citation